Harnessing Adaptive Leadership to Manage Workplace Diversity for Organizational Productivity: A Literature Review Approach - Prasetya, Ferdyana Eka; Anas, Muhamad Abdul; Khairunisa, Nadya; Ekhsan, Muhamad (Review: Journal of Multidisciplinary in Social Sciences, 2025)
In an increasingly competitive business world, leadership strategies to improve performance depend heavily on the quality of human resources. Diversity in the workplace is an unavoidable reality in the era of globalization, where technological advances and labor mobility have opened up opportunities for interaction between individuals from various cultural backgrounds, religions, ages, and life experiences. When diversity is not managed properly, it can cause misunderstandings, conflicts, and even discrimination, which hinder productivity and lower employee morale. The purpose of this study is to analyze in depth the application of adaptive leadership strategies in managing employee diversity to improve organizational productivity. This research uses a qualitative approach with literature review methods. The results of the study show that adaptive leadership plays an important role in creating an inclusive, collaborative, and harmonious work environment, through open communication, flexibility in approach, and employee empowerment. These findings imply that organizations aiming to boost performance in a diverse workforce environment should prioritize leadership development programs that embrace adaptability and cultural intelligence. Therefore, it can be concluded that adaptive leadership is an effective strategy in dealing with the complexity of diversity in the modern workplace, but it is also a strategic key in increasing competitiveness and ensuring long-term sustainability.